2023
DOI: 10.1038/s41467-023-37537-2
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination deficiency derived from whole-genome sequencing predicts platinum response in triple-negative breast cancers

Abstract: The high frequency of homologous recombination deficiency (HRD) is the main rationale of testing platinum-based chemotherapy in triple-negative breast cancer (TNBC), however, the existing methods to identify HRD are controversial and there is a medical need for predictive biomarkers. We assess the in vivo response to platinum agents in 55 patient-derived xenografts (PDX) of TNBC to identify determinants of response. The HRD status, determined from whole genome sequencing, is highly predictive of platinum respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…Secondly, the in vitro drug screening assays examined in the cell line databases evaluated drug response over a very short period of 3–5 days, which is considerably shorter than the assessment of efficacy in vivo or in clinical tumors, where it is usually assessed on a weekly or monthly basis. In a report using patient-derived xenografts (PDX), it took at least 10 days for platinum to achieve effective tumor suppression in HRD tumors 23 . This suggests that differences between in vitro and in vivo assays may contribute to the observed discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the in vitro drug screening assays examined in the cell line databases evaluated drug response over a very short period of 3–5 days, which is considerably shorter than the assessment of efficacy in vivo or in clinical tumors, where it is usually assessed on a weekly or monthly basis. In a report using patient-derived xenografts (PDX), it took at least 10 days for platinum to achieve effective tumor suppression in HRD tumors 23 . This suggests that differences between in vitro and in vivo assays may contribute to the observed discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Pt-based anticancer drugs exhibit severe toxicity and induce tumor immunosuppression in clinical application. Improving the binding efficiency between platinum drugs and DNA through a nuclear-targeting strategy has emerged as an effective strategy to reduce toxicity and enhance efficiency. The immunosuppression induced by chemotherapy is an important factor in causing tumor recurrence .…”
Section: Discussionmentioning
confidence: 99%
“…However, PARPis are currently only approved in both early [24] and metastatic [101,102] settings of TNBC for germline carriers of BRCA1 and BRCA2 pathogenic variants. Interestingly, some studies have suggested that also patients carrying genetic alterations in other HR/DDR genes [103,104 ▪ ] as well as those with HRD-high tumor phenotype [105,106] might benefit from HR/DDR targeting. Trials are underway to target BRCAness or HRD-deficient tumors, including TNBC (Table 5).…”
Section: Mutational Signaturesmentioning
confidence: 99%